Strategi Lembaga Masyarakat Adat Menjaga Stabilitas Sosial Budaya Di Kabupaten Fakfak Provinsi Papua Barat - Akbar Zuhair Rafsanjani Pagesa; M. Sari (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The author focuses on the problem of how the Indigenous Peoples' Institution of Fakfak Regency resolves a problem or dispute, seen from its strategy. This institution, which was established in 2012, has had problems such as the absence of reports regarding the activities carried out by Indigenous Peoples' Institutions. This is due to a lack of coordination between Indigenous Peoples' Institutions as community organizations and the agency that oversees them, namely the Fakfak District Politics and National Unity Agency. The purpose of this research is to find out the strategy of Indigenous Peoples' Institutions in maintaining socio-cultural stability in Fakfak Regency and to find out the supporting factors and inhibiting factors of Indigenous Peoples' Institutions' strategy in maintaining socio- cultural stability in Fakfak Regency. The research method in this research is descriptive qualitative research with an inductive approach. Data collection techniques through interviews, observation, and documentation. in order to know these objectives, the theory of strategy according to Arthur Lyyke is used. According to Lyyke there are 3 (three) dimensions, namely Method, Source, and Purpose. The results of the research show that the strategy of Indigenous Peoples' Institutions in maintaining socio-cultural stability in Fakfak Regency is divided into 3 dimensions, namely the goal dimension in short- term goal indicators is not optimal due to the non-involvement of Kesbangpol in the formulation of these goals. In the second dimension, resources, namely the involvement of all parties is optimal so that understanding from various perspectives is obtained. The third dimension, the LMA's way of resolving disputes is appropriate, this is shown by summoning the reporting party and the reported party then identifies the problem by tracing related documents. Then the appropriate decision is decided. The results of this study show that the strategy carried out by the Indigenous Peoples' Institution of Fakfak Regency is not as good as the strategy theory by Arthur Lyyke. In an effort to overcome this, it is suggested that the Fakfak Regency LMA coordinate with the Fakfak Regency Kesbangpol so that there is involvement between the two organizations. This is so that Kesbangpol can participate in the goal formulation process carried out by LMA